Cry until you laugh : comforting guidance for coping with grief - Obershaw, Richard J., 1944- (Fairview Press, 1992)
Blending gentle humor with practical advice for the bereaved, Dick Obershaw confronts our expectations, myths, attitudes, and prejudices about grief and loss. His down-to-earth approach has already helped thousands of people come to terms with their grief.